Better Life’s Essential 8 contributes to slowing the biological aging process: a cross-sectional study based on NHANES 2007–2010 data - Wu, Dongzhe; Qu, Chaoyi; Huang, Peng; Geng, Xue; Zhang, Jianhong; Shen, Yulin; Rao, Zhijian; Zhao, Jiexiu (Frontiers in Public Health, 2024)
Objective: This study examines the correlation between Life's Essential 8 (LE8) and Phenotypic Age Acceleration (PhenoAgeAccel) among U.S. adults to assess the impact of LE8 on biological aging, offering insights for public health strategies. Methods: Data from 7339 participants aged 20+ in the 2007-2010 National Health and Nutrition Examination Survey (NHANES) were analyzed using weighted generalized linear regression and restricted cubic spline plots to explore linear and non-linear relationships between LE8 and PhenoAgeAccel, including gender-specific analyses. Results: Analysis of NHANES participants divided into LE8 quartiles highlighted significant differences in demographic and health variables. Higher LE8 quartiles correlated negatively with PhenoAgeAccel in adjusted models (P<0.05), with significant trends observed in both genders (P<0.001 for males, P = 0.001 for females). No significant non-linear trends or interaction effects were found, except for BMI and diabetes status, which showed interaction effects (P<0.05). Conclusion: Higher LE8 scores are significantly associated with reduced PhenoAgeAccel, underscoring the role of healthy lifestyle choices in mitigating biological aging. Despite its limitations, this study provides a foundation for health policy focused on lifestyle interventions, warranting further research on the causal relationships and cross-cultural applicability of these findings.